2018
DOI: 10.1186/s13046-018-0864-6
|View full text |Cite
|
Sign up to set email alerts
|

LGR5, a novel functional glioma stem cell marker, promotes EMT by activating the Wnt/β-catenin pathway and predicts poor survival of glioma patients

Abstract: BackgroundTumor recurrence, the chief reason for poor prognosis of glioma, is largely attributed to glioma stem cells (GSCs) and epithelial-mesenchymal transition (EMT). However, the mechanisms among them remain unknown. Here, we determined whether leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5), known as a stem cell marker for colon cancer and gastric cancer, can serve as a novel GSC marker involved in EMT and a therapeutic target in glioma.MethodsStemness properties were examined in FACS-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 43 publications
5
102
0
Order By: Relevance
“…PKCζ affects β‐catenin stability, further affecting stem cell function . The Wnt/β‐catenin pathway plays an important role in tumor cell EMT and stemness; such report is consistent with our results from KEGG pathway analysis based on the differential genes between cPLA2α KD and KD/SCR CSCs and from mass spectrometry analysis. Many β‐catenin molecules bound to the cytomembrane with E‐cadherin, and less nuclear translocation of β‐catenin occurred when PKCζ was knocked down regulated by cPLA2α inhibition, leading to increased E‐cadherin‐mediated cell‐to‐cell adhesion and blockage of EMT and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…PKCζ affects β‐catenin stability, further affecting stem cell function . The Wnt/β‐catenin pathway plays an important role in tumor cell EMT and stemness; such report is consistent with our results from KEGG pathway analysis based on the differential genes between cPLA2α KD and KD/SCR CSCs and from mass spectrometry analysis. Many β‐catenin molecules bound to the cytomembrane with E‐cadherin, and less nuclear translocation of β‐catenin occurred when PKCζ was knocked down regulated by cPLA2α inhibition, leading to increased E‐cadherin‐mediated cell‐to‐cell adhesion and blockage of EMT and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…The Wnt signaling pathway is an evolutionarily conserved developmental signaling cascade that plays a critical role in regulating organ development and tissue homeostasis. Leucine‐rich repeat‐containing G protein‐coupled receptor 5 (LGR5) is a novel functional marker in glioma stem cells that promotes EMT by activating the Wnt/β‐catenin signaling pathway . Sry‐like high‐mobility group box 8 regulated cancer stem‐like properties and cisplatin‐induced EMT by the Wnt/β‐catenin signaling pathway in tongue squamous cell carcinoma .…”
Section: Small Molecules Against Emtmentioning
confidence: 92%
“…(LGR5) is a novel functional marker in glioma stem cells that promotes EMT by activating the Wnt/β-catenin signaling pathway. 138 Sry-like high-mobility group box 8 regulated cancer stem-like properties and cisplatin-induced EMT by the Wnt/β-catenin signaling pathway in tongue squamous cell carcinoma. 139 In addition, bone marrow mesenchymal stromal cells suppressed EMT by inhibiting the Wnt/β-catenin signaling pathway in silica-induced pulmonary fibrosis.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…This is consistent with a former work that suggested miR‐150‐5p suppressed chemoresistance in ovarian cancer cells (Xia et al, 2017). In addition, the Wnt/β‐catenin pathway has been reported to regulate the population of glioma stem cells (Hsieh et al, 2013; Zhang et al, 2018a). These results indicated that miR‐150‐5p suppressed the characteristics of glioma stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β‐catenin pathway regulates cell invasion, proliferation, and apoptosis in glioma cells via varying mechanisms (Gao et al, 2017). Moreover, the Wnt/β‐catenin pathway is associated with epithelial–mesenchymal transition and prognosis of glioma patients (Zhang et al, 2018a). Besides, catenin beta 1 (CTNNB1, which encodes β‐catenin) has been suggested as one of the key transducers in the Wnt/β‐catenin pathway (Su et al, 2012).…”
Section: Introductionmentioning
confidence: 99%